2011
DOI: 10.1111/j.1349-7006.2011.01980.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastrointestinal follicular lymphoma involving the duodenal second portion is a distinct entity: A multicenter, retrospective analysis in Japan

Abstract: We conducted a multicenter, retrospective study to determine the anatomical distribution and prognostic factors of gastrointestinal (GI) follicular lymphoma (FL). This study included 125 patients with stage I and II 1 GI-FL. Of the 125 patients, the small intestine was examined in 70 patients, with double-balloon endoscopy and ⁄ or capsule endoscopy. The most frequently involved GI-FL site was the duodenal second portion (DSP) (81%), followed by the jejunum (40%); 85% of patients with involvement of the DSP al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
186
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(202 citation statements)
references
References 23 publications
13
186
1
2
Order By: Relevance
“…Although the duodenal second portion is the most frequent site of FL in the gastrointestinal tract, 3,4 it sometimes occurs primarily in the gastrointestinal tract outside of the duodenum. Using double-balloon and/or capsule endoscopy, FLs of the gastrointestinal tract primarily involve the duodenum and frequently spread to the small intestine, 3 Few FLs occur in the stomach and colon, but the clinicopathological features of FL in such organs remain unclear.…”
mentioning
confidence: 99%
“…Although the duodenal second portion is the most frequent site of FL in the gastrointestinal tract, 3,4 it sometimes occurs primarily in the gastrointestinal tract outside of the duodenum. Using double-balloon and/or capsule endoscopy, FLs of the gastrointestinal tract primarily involve the duodenum and frequently spread to the small intestine, 3 Few FLs occur in the stomach and colon, but the clinicopathological features of FL in such organs remain unclear.…”
mentioning
confidence: 99%
“…Patients with grade 3 follicular lymphoma were excluded from this study because these cases are typically managed as cases of diffuse large B-cell lymphoma (1). A subset of the 12 patients examined herein were also subjects of our previous studies (4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely accepted that follicular lymphoma typically arises in the lymph nodes along with spleen, liver, and bone marrow involvement (1,2). However, several studies have revealed that follicular lymphoma primarily or secondarily affects the gastrointestinal tract as well (3)(4)(5). Involvement of the small intestine, especially the duodenum, is a predominant feature of intestinal presentation in follicular lymphoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It typically presents in the second portion of the duodenum, and less-frequently, in the jejunum 1 and appears endoscopically as one or more small polyps. Although typically asymptomatic, it may present with bowel obstruction.…”
Section: Reports Of Cases and Pathologic Findings Casementioning
confidence: 99%